Kamal Ibrahim's Approach and Thought in Linguistic Criticism - Dr. Wissam Ghali Gati (Journal of College of Education, 2023)
This research deals with a scholar of   Arabic language and literature in Iraq, and one of those prominent critics   , who tried to contribute to  serving Arabic and  preserving its identity from foreignness and deviation in its rules and formulations.                                                                                                                 This scholar is Professor, Kamal Ibrahim. The research has shown the approach adopted by this critic in the field of linguistic criticism, the thought predominant in his critiques and what scale of validity he used to judge whether the Arabic linguistic  uses are correct or false. It was shown that he is one of the adherents of the strict approach in language criticism, an approach that aims at the production of the most eloquent discourse, and makes everything else mistaken and a mere  influence  by former adherents  of this trend ,such as Al-Yazji and Dagher, and following them in criticisms. We have selected examples of his critiques to illustrate his trend  and critical thought
Keywords: Kamal Ibrahim, mistakes of the book, scale of validity, critical approach, linguistic corrections.